2005
DOI: 10.1002/chem.200400678
|View full text |Cite
|
Sign up to set email alerts
|

A Unified Orbital Model of Delocalised and Localised Currents in Monocycles, from Annulenes to Azabora‐heterocycles

Abstract: Why are some (4n+2)π systems aromatic, and some not? The ipsocentric approach to the calculation of the current density induced in a molecule by an external magnetic field predicts a four‐electron diatropic (aromatic) ring current for (4n+2)π carbocycles and a two‐electron paratropic (antiaromatic) current for (4n)π carbocycles. With the inclusion of an electronegativity parameter, an ipsocentric frontier‐orbital model also predicts the transition from delocalised currents in carbocycles to nitrogen‐localised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
70
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 43 publications
5
70
0
2
Order By: Relevance
“…Subtleties of the adaptation of the pseudo-p method for hetero-A C H T U N G T R E N N U N G atoms have been discussed elsewhere. [27] In passing, we may note that the ipsocentric method gives a direct interpretation of the maps as they are seen, that is, it interprets the perimeter current. In contrast, graph-theoretical models that decompose the current into circuit contributions [28, 8b] would interpret the plotted perimeter current as a summation of superimposed diatropic benzene-and naphthalene-circuit contributions that cancel out everywhere except on the perimeter, plus a weak paratropic perimeter-circuit contribution.…”
Section: Resultsmentioning
confidence: 99%
“…Subtleties of the adaptation of the pseudo-p method for hetero-A C H T U N G T R E N N U N G atoms have been discussed elsewhere. [27] In passing, we may note that the ipsocentric method gives a direct interpretation of the maps as they are seen, that is, it interprets the perimeter current. In contrast, graph-theoretical models that decompose the current into circuit contributions [28, 8b] would interpret the plotted perimeter current as a summation of superimposed diatropic benzene-and naphthalene-circuit contributions that cancel out everywhere except on the perimeter, plus a weak paratropic perimeter-circuit contribution.…”
Section: Resultsmentioning
confidence: 99%
“…As will be explained below, this model relies on a matching in symmetry between the carbon π orbitals responsible for ring currents and the σ orbitals of a set of hydrogen atoms that has the same connectivity. In previous work, the pseudo-π model has been shown to reproduce qualitatively and even semi-quantitatively the patterns of induced current density in planar and near-planar aromatic, antiaromatic and non-aromatic systems, giving yes/no answers to the question of aromaticity and an account of the origins of the ring current (if any) in terms of orbital contributions, all at a tiny fraction of the cost of a full ab initio treatment [36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 98%
“…While many earlier studies suggested that borazine is highly aromatic, the most recent theoretical results suggest just the opposite. [10,11] Thus, the matter is still one of debate and study.…”
mentioning
confidence: 99%